Diversity, Distribution, and Density of Marine Mammals Along the Saudi Waters of the Arabian Gulf: Update From a Multi-Method Approach - Rabaoui, Lotfi; Roa-Ureta, Ruben H.; Yacoubi, Lamia; Lin, Yu-Jia; Maneja, Rommel; Joydas, Thadickal V.; Panickan, Premlal; Gopalan, Jinoy; Loughland, Ronald; Prihartato, Perdana K.; Qassem, Ali; Hikmawan, Tyas I.; et al. (Frontiers in Marine Science, 2021)
Despite the important role of marine mammals in marine ecosystems and the imperative for their conservation, there is still a great lack of information on the diversity, distribution, and density of these animals in the Saudi waters of the Arabian Gulf. To fill this gap, an integrative data-collection approach including fishermen’s questionnaires, opportunistic sighting reports, and directed boat-based surveys, was undertaken between 2016 and 2020, leading to the first scientific report of marine mammal diversity, distribution, and density in the region. The results of the different approaches carried out during the study confirmed a high diversity of cetaceans on the west coast of the study area, with bottlenose dolphins (Tursiops aduncus), humpback dolphins (Sousa plumbea) and dugongs (Dugong dugon) as the most common species. While the two dolphin species were found to be widely distributed in both coastal and offshore waters, D. dugon appears to occur exclusively in coastal waters in the southern part of the study area, mainly in the Gulf of Salwah. The presence of both species of dolphins increased during the summer months and in the vicinity of the numerous oil and gas facilities in this region. The distribution of the observed dolphins was found mostly within a 10–20 km radius around each facility. Other cetacean species observed less frequently in the area include Bryde’s whale (Balaenoptera edeni), killer whale (Orcinus orca), common dolphin (Delphinus delphis) and finless porpoise (Neophocaena phocaenoides). Regarding the density of marine mammals in the region, boat-based surveys confirmed the results of fishermen’s questionnaires and reports of opportunistic sightings, with bottlenose and humpback dolphins being the most abundant species. These results provide a baseline for policies oriented to the conservation of mammals in the Saudi waters of the Arabian Gulf.